Impact of SARS-CoV-2 on Onset of Diabetes and Associated Complications - Piracha, Zahra Zahid; Saeed, Umar; Sarfraz, Rameesha; Asif, Urooj; Waheed, Yasir; Raheem, Ayesha; Tahir, Maida; Kiran, Saleha; Pervaiz, Iqra; Uppal, Rizwan (Archives of Clinical and Biomedical Research, 2022)
Today, diabetes mellitus and COVID-19 are major worldwide health issues. After several researches, it has been concluded that patients already having diabetes have more chances to be affected by coronavirus. Human pancreas has been suggested as a target of SARS-CoV-2 and it is also suggested that beta cell infection could contribute to the metabolic dysregulation observed in patients with COVID-19. Taken together, our review data indicate that a COVID-19 infection can cause major prolix health problems, like lung damage and even can cause sudden onset of insulin-dependent diabetes. Here in our review article, we have listed case reports along with the mechanistic review of molecular interactions and immunomodulation. Our review has brought out the relation between glucose lowering drugs and COVID-19 and major studies about inflammation and insulin inflammation.